2022
DOI: 10.1186/s12940-022-00884-6
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the undermining of science and health policy after the Fukushima nuclear accident by applying the Toolkit for detecting misused epidemiological methods

Abstract: It is well known that science can be misused to hinder the resolution (i.e., the elimination and/or control) of a health problem. To recognize distorted and misapplied epidemiological science, a 33-item “Toolkit for detecting misused epidemiological methods” (hereinafter, the Toolkit) was published in 2021. Applying the Toolkit, we critically evaluated a review paper entitled, “Lessons learned from Chernobyl and Fukushima on thyroid cancer screening and recommendations in the case of a future nuclear accident”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(42 citation statements)
references
References 63 publications
1
40
1
Order By: Relevance
“…It seems better to compare the dose dependence of EAR/PY than ERR/Gy among nuclear accidents if thyroid dose was not measured directly as in Fukushima. [7]. They proposed the need for alternative measurements of thyroid dose, such as the incidence of childhood thyroid cancer, owing to the large gap among the estimates, ranging from less than 1 mSv to more than 1000 mSv.…”
Section: Much Higher Err/gy In Fukushima Than In Chernobylmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems better to compare the dose dependence of EAR/PY than ERR/Gy among nuclear accidents if thyroid dose was not measured directly as in Fukushima. [7]. They proposed the need for alternative measurements of thyroid dose, such as the incidence of childhood thyroid cancer, owing to the large gap among the estimates, ranging from less than 1 mSv to more than 1000 mSv.…”
Section: Much Higher Err/gy In Fukushima Than In Chernobylmentioning
confidence: 99%
“…Thyroid doses in Chernobyl were based on 350,000 direct thyroid dose measurements performed after the Chernobyl accident (B35) [6]. On the other hand, in Fukushima, only 1080 thyroid monitoring was carried out outside the evacuation zone by the use of a less-sensitive survey meter [7]. The measurements might have been a great underestimation because 55% of measured thyroid doses were negative or zero, suggesting that some doses other than background were subtracted from the measurements (A135,136, Table A20) [2].…”
Section: Introductionmentioning
confidence: 99%
“…We welcome the suggestion by Tsuda et al [1] that the items in Part A (i.e., method-related misuses) of the Toolkit [2] be rearranged in the order of how a study is designed, conducted, analyzed, and reported. This could help other potential users of the Toolkit navigate through all of the items.…”
Section: Response To Recommendations To Improve the Toolkitmentioning
confidence: 98%
“…A year after publication of our Toolkit article [2], not only do we see its application by Tsuda et al [1] in the field of Epidemiology, but now, a few weeks later in Conservation Letters, a journal of the Society for Conservation Biology, our Toolkit is seen to have inspired its authors to fashion it for use in the Biological Sciences [9]. Burgman et al [9] have used our Toolkit [2] as a starting point and adapted the items to reflect issues of special relevance to Conservation Biology, focusing on issues that are relevant in conservation and environmental science.…”
Section: Postscriptmentioning
confidence: 99%
See 1 more Smart Citation